Clinical characteristics of oral squamous cell carcinoma metastasis (Research, Society and Development, 2020)
The incidence of oral cancer in Brazil is considered to be one of the highest in the world, being considered the most common cancer of the head and neck region, excluding non-melanoma skin cancer. Squamous cell carcinoma, also known as squamous cell carcinoma, is the most common and recurrent type of oral cancer, accounting for more than 90% of cases. The great evolutionary ability of the cancerous tumor lies in the distancing from the primary tumoral focus, due to its ability to spread to other organs and tissues. Such a condition is called metastasis, specifically when cancer cells are found in the bloodstream or lymphatic vessels and assume an evolutionary posture lodging in different parts of the body. Diagnosing any lymph node or distant metastasis from oral cancer is very important for the patient's prognosis. The present study is a literary review, in which we try to explain some classic and recent concepts of metastasis of oral cancer, in order to predict the possibility of an event in patients with squamous cell carcinoma.